2018
DOI: 10.1038/s41598-018-27786-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing human subchondral bone properties using near-infrared (NIR) spectroscopy

Abstract: Degenerative joint conditions are often characterized by changes in articular cartilage and subchondral bone properties. These changes are often associated with subchondral plate thickness and trabecular bone morphology. Thus, evaluating subchondral bone integrity could provide essential insights for diagnosis of joint pathologies. This study investigates the potential of optical spectroscopy for characterizing human subchondral bone properties. Osteochondral samples (n = 50) were extracted from human cadaver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Correlations between NIR absorption measurements and bone properties are supported by both the cadaver and MC modeling studies, which indicate that a reflectance NIR probe is capable of sampling M2 bone transcutaneously, with 45% to 50% of the measured spectra's contribution arising directly from the bone. The relationship between direct (ie, not transcutaneous) NIR absorption measures of bone and bone quality has been shown in prior studies, where NIR spectra correlated to subchondral bone morphometric properties as determined by micro‐computed tomography in samples extracted from rats and humans . However, the exponential attenuation of light through absorbing tissues suggests that absorption from the overlying skin, fascia and fat could dominate that from the underlying bone, thus eliminating any correlations between transcutaneous NIR absorption measurements and bone quality.…”
Section: Discussionmentioning
confidence: 81%
“…Correlations between NIR absorption measurements and bone properties are supported by both the cadaver and MC modeling studies, which indicate that a reflectance NIR probe is capable of sampling M2 bone transcutaneously, with 45% to 50% of the measured spectra's contribution arising directly from the bone. The relationship between direct (ie, not transcutaneous) NIR absorption measures of bone and bone quality has been shown in prior studies, where NIR spectra correlated to subchondral bone morphometric properties as determined by micro‐computed tomography in samples extracted from rats and humans . However, the exponential attenuation of light through absorbing tissues suggests that absorption from the overlying skin, fascia and fat could dominate that from the underlying bone, thus eliminating any correlations between transcutaneous NIR absorption measurements and bone quality.…”
Section: Discussionmentioning
confidence: 81%
“…The superior penetration depth of NIRS, compared to MIRS, promotes its application for evaluation of whole cartilage tissue in clinical arthroscopies. In contrast to MIRS, NIRS is also capable of providing information on the underlying bone through articular cartilage in both equine and humans 1,27. These studies showed that the visible and short NIR spectral regions are optimal for estimating bone properties, such as subchondral plate thickness and volume fraction, due to their better penetration depth compared to longer wavelengths 20…”
Section: Discussionmentioning
confidence: 99%
“…Most probably the spectral response from the superficial cartilage layer, which substantially contributes to cartilage biomechanical capacity, is sufficient for accurate prediction of biomechanical properties. Although spectral region could be restricted to 1,400e2,500 nm, as per Padalkar et al 39 , to limit the effects of subchondral bone 43 , the benefits of utilizing wider spectral region in terms of improved correlation with biomechanical properties and compositional properties outweigh its cons 23,44 .…”
Section: Discussionmentioning
confidence: 99%